Rodent Brain Slice Model for the Study of White Matter Injury - Murata, Akira (2013)
OBJECTIVE: Cerebral white matter (WM) injury is common after cardiac surgery in neonates and young infants who have brain immaturity and genetic abnormalities. In order to understand better the mechanisms associated with WM injury, we tested the adequacy of a novel ex-vivo brain slice model, with a particular focus on how the maturational stage modulates the injury. METHODS: To replicate conditions of cardiopulmonary bypass living brain slices were transferred to a closed chamber perfused by artificial cerebrospinal-fluid under controlled temperature and oxygenation. Oxygen-glucose deprivation (OGD) simulated circulatory arrest. The effects of maturation were investigated in 7 and 21-day-old mice (P7, P21) that are equivalent in maturation stage to the human fetus and young adult. RESULTS: There were no morphological changes in axons after 60 min OGD at 15°C in both P7 and P21 WM. Higher temperature and longer duration of OGD were associated with significantly greater WM axonal damage, suggesting that the model replicates the injury seen after hypothermic circulatory arrest. The axonal damage at P7 was significantly less than at P21 demonstrating that immature axons are more resistant than mature axons. Conversely, a significant increase in caspase3(+) oligodendrocytes in P7 mice was identified relative to P21, indicating that oligodendrocytes in immature WM are more vulnerable than oligodendrocytes in mature WM. CONCLUSIONS: Neuroprotective strategies for immature WM may need to focus on reducing oligodendrocyte injury. The brain slice model will be helpful in understanding the effects of cardiac surgery on the immature brain and the brain with genetic abnormalities.